Herpes zoster in healthy children: the innocent face of controversy - Pereira, Tânia (2015)
Introduction: Herpes zoster (HZ) emerges sporadically by reactivation of the varicella zoster virus (VZV). It lies latent within the dorsal root of sensory ganglia or cranial nerves after primary infection, which manifests clinically as varicella. Its incidence increases with age and is rare in childhood. Case report: We describe the case of a 9-year-old previously healthy male, brought to medical consultation for pain and vesicular exanthema in the T1 dermatome, compatible with HZ. He was treated with acyclovir and improved clinically after three weeks. Discussion: In healthy children, HZ is rare. The main risk factor for childhood onset of HZ is primary VZV infection during gestation or the first year of life. It is not necessary to exclude underlying immunodeficiency, except in cases of recurrence. Due to its characteristics, childhood HZ is a disease that raises questions at diagnosis and regarding appropriate treatment.